Mental Readiness and Challenges faced by Health care Front liners during COVID-19 Pandemic in Malaysia - Siti Hajar Johari; Abu Yazid Abu Bakar; Salleh Amat; Kadek Suranata (Department of Guidance and Counseling, FIP, Undiksha, 2021)
The readiness and mental challenges of health care front-liners are one of the big issues that need to be addressed by the Ministry of Health Malaysia (MOH) and also the Malaysian Board of Counselors (MBC). This is to ensure that all threats to health care front-liners can be overcome in order to streamline the duties of fighting the COVID-19 pandemic in Malaysia. Therefore, this study aims to understand the readiness and mental challenges of health front workers (Font liners) in facing the COVID-19 pandemic. This study uses a qualitative design with a case study approach. The study participants consisted of two medical officers and two nurses from the states of Johor and Sabah who had more than six months of experience in handling COVID-19 cases. Study data were obtained through semi-structured interview techniques. The findings state that there are two sub-theme codes from the mental readiness of health care front liners and four subtrahend codes from the mental challenges of health care front liners in facing the COVID-19 pandemic. Information from this study can be used by the MOH and MBC in dealing with the possible mental health issues of the health care front liner, post-COVID-19 in Malaysia.